Discovery of the Potentiator of the Pore-Forming Ability of Lantibiotic Nisin: Perspectives for Anticancer Therapy - Dayana N. Chernyshova; Alexander A. Tyulin; Olga S. Ostroumova; Svetlana S. Efimova (Membranes, 2022)
This study was focused on the action of lantibiotic nisin on the phospholipid membranes. Nisin did not produce ion-permeable pores in the membranes composed of DOPC or DOPE. The introduction of DOPS into bilayer lipid composition led to a decrease in the threshold detergent concentration of nisin. An addition of nisin to DOPG- and TOCL-enriched bilayers caused the formation of well-defined ion pores of various conductances. The transmembrane macroscopic current increased with the second power of the lantibiotic aqueous concentration, suggesting that the dimer of nisin was at least involved in the formation of conductive subunit. The pore-forming ability of lantibiotic decreased in the series: DOPC/TOCL ≈ DOPE/TOCL >> DOPC/DOPG ≥ DOPE/DOPG. The preferential interaction of nisin to cardiolipin-enriched bilayers might explain its antitumor activity by pore-formation in mitochondrial membranes. Small natural molecules, phloretin and capsaicin, were found to potentiate the membrane activity of nisin in the TOCL-containing membranes. The effect was referred to as changes in the membrane boundary potential at the adsorption of small molecules. We concluded that the compounds diminishing the membrane boundary potential should be considered as the potentiator of the nisin pore-forming ability that can be used to develop innovative formulations for anticancer therapy.